Identification of a PRMT5-dependent repressor complex linked to silencing of human fetal globin gene expression - Rank, Gerhard (American Society of Hematology, 2010)
Defining the molecular mechanisms underpinning fetal (γ) globin gene silencing may provide strategies for reactivation of γ-gene expression, a major therapeutic objective in patients with β-thalassemia and sickle cell disease (SCD). We have previously demonstrated that symmetric methylation of histone H4 Arginine 3 (H4R3me2s) by the protein arginine methyltransferase PRMT5 is required for recruitment of the DNA methyltransferase DNMT3A to the γ-promoter, and subsequent DNA methylation and gene silencing. Here we show in an erythroid cell line, and in primary adult erythroid progenitors that PRMT5 induces additional repressive epigenetic marks at the γ-promoter through the assembly of a multiprotein repressor complex containing the histone modifying enzymes SUV4-20h1, casein kinase 2α (CK2α), and components of the nucleosome remodeling and histone deacetylation complex. Expression of a mutant form of PRMT5 lacking methyltransferase activity or shRNA-mediated knockdown of SUV4-20h1 resulted in loss of complex binding to the γ-promoter, reversal of both histone and DNA repressive epigenetic marks, and increased γ-gene expression. The repressive H4K20me3 mark induced by SUV4-20h1 is enriched on the γ-promoter in erythroid progenitors from adult bone marrow compared with cord blood, suggesting developmental specificity. These studies define coordinated epigenetic events linked to fetal globin gene silencing, and provide potential therapeutic targets for the treatment of β-thalassemia and SCD.